SERPENTINIZATION AND DEHYDRATION IN THE UPPER MANTLE BENEATH FUERTEVENTURA (EASTERN CANARY ISLANDS): EVIDENCE FROM MANTLE XENOLITHS - Abu El-Rus M.A.; Neumann E.-R.; Peters V. (My University, 2006)
Mantle xenoliths from Fuerteventura (spinel-bearing harzburgites, dunites, and rare lherzolites and wehrlites) in the easternmost part of the Canary Islands chain, are highly deformed and show a wide range in textures from protogranular and porphyroclastic with olivine and orthopyroxene porphyroclasts, to rocks with "fibrous textures" (no orthopyroxene porphyroclasts, large, porous clusters of fibrous orthopyroxene, olivine porphyroclasts criss-crossed by stringy trails of fibrous orthopyroxene and fluid inclusions). The whole group of xenoliths covers a wider compositional range (e.g. Fo86.6-92.7, 0.18-0.44 wt.% NiO, and up to 0.25 wt.% CaO in olivine; < 0.01-2.5 wt.% TiO2 and 0.7-5.5 wt.% Al2O3 in clinopyroxenes in harzburgites and lherzolites, and relatively Ti-Fe3+-rich spinels in some rocks). Rocks with orthopyroxene porphyroclasts cover a restricted compositional range typical of depleted oceanic peridotites (e.g. Fo90.7-91.4, 0.36-0.41 wt.% NiO, and < 0.10 wt.% CaO in cores of olivine porphyroclasts; ≤ 0.12 wt.% TiO2, 1.0-1.8 wt.% Al2O3 in clinopyroxene; low Ti and Fe3+, and high Cr in spinel). These rocks are interpreted as pieces of the highly refractory oceanic lithosphere that accreted to the oldest oceanic crust in this part of the Atlantic Ocean, later modified by different processes. This mantle was highly depleted due to melt extraction, and had a composition similar to that of the most refractory peridotites collected along the Mid-Atlantic Ridge. Also the oceanic mantle beneath the other Canary Islands appears to have had similar composition before the onset of the Canary Islands magmatism. The "fibrous textures" in many xenoliths from Fuerteventura are interpreted as the results of partial serpentinization, later followed by heating and dehydration during the formation of Fuerteventura. The Fuerteventura magmatism has also caused metasomatism and reactions in the lithospheric mantle beneath Fuerteventura, leading to decreased Si and increased Fe+Ca+Na±Ti. © 2005 Elsevier B.V. All rights reserved.
Keywords: CANARY ISLAND; DEHYDRATION; METASOMATISM; PETROGENESIS; SERPENTINIZATION